Contrast Time‐Density Time on Digital Subtraction Angiography Correlates With Cerebral Arteriovenous Malformation Flow Measured by Quantitative Magnetic Resonance Angiography, Angioarchitecture, and Hemorrhage. Issue 2 (August 2018) - Brunozzi, Denise; Hussein, Ahmed E; Shakur, Sophia F; Linninger, Andreas; Hsu, Chih‐Yang; Charbel, Fady T; Alaraj, Ali
Abstract : BACKGROUND : Digital subtraction angiography (DSA) currently provides angioarchitectural features of cerebral arteriovenous malformations (AVMs) but its role in the hemodynamic evaluation of AVMs is poorly understood. OBJECTIVE : To assess contrast time‐density time (TT) on DSA relative to AVM flow measured using quantitative magnetic resonance angiography (QMRA). METHODS : Patients seen at our institution between 2007 and 2014 with a supratentorial AVM and DSA and QMRA obtained prior to any treatment were retrospectively reviewed. Regions of interest were selected on the draining veins at the point closest to the nidus. TT on DSA was defined as time needed for contrast to change image intensity from 10% to 100%, 100% to 10%, and 25% to 25%. TT was correlated to AVM total flow, angioarchitectural features, and hemorrhage. RESULTS : Twenty‐eight patients (mean age 35.6 yr) were included. Six patients presented with hemorrhage. Mean AVM volume was 11.42 mL (range 0.3‐57.7 mL). Higher total AVM flow significantly correlated with shorter TT100%‐10% and TT25%‐25% ( P = .02, .02, respectively). Presence of venous stenosis correlated significantly with shorter TT100%‐10% ( P = .04) and TT25%‐25% ( P = .04). AVMs with a single draining vein exhibited longer TT25%‐25% compared to those with multiple draining veins ( P = .04). Ruptured AVMs had significantly shorter TT10%‐100% compared to unruptured AVMs ( P = .05). CONCLUSION : TT on DSA correlates with cerebral AVM flow measured using QMRA and with AVM angioarchitecture and hemorrhagic presentation. Thus, TT may be used to indirectly estimate AVM flow during angiography in real‐time and may also be an indicator of important AVM characteristics associated with outflow resistance and increased rupture risk, such as venous stenosis.